ERT Challenges in the Post-2015 Era - Ahmed, Manzoor (Journal of Education and Research, 2015)
This paper provides a background to the on-going discourse on post-2015 global development agenda. It mentions key points from the UN Secretary General’s report on MDG progress and the process of formulating the future development agenda. The recommendations of the High Level Panel on post-2015 agenda and the work of the Sustainable Development Solutions Network (SDSN) are examined from the perspective of Education for Rural Transformation (ERT). It is concluded that the premise and rationale of ERT has received scant attention in the future development agenda discourse. The arguments regarding the pertinence of ERT in combating poverty and promoting sustainable development are noted, drawing on the recent UNESCO- INRULED study on this topic.